1989
DOI: 10.1111/j.1365-2125.1989.tb05332.x
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐adrenoceptors and human skeletal muscle characterisation of receptor subtype and effect of age.

Abstract: 1 Rectus abdominis muscle biopsies were obtained from 28 patients undergoing abdominal surgery. In membranes prepared from these biopsies ,-adrenoceptor binding was examined. The apparent affinity (KD) and the density (Bmax) of the receptors for the radioligand (_)_[1251 cyanopindolol were 28.5 ± 2.7 (pM) and 25.9 ± 2.1 (fmol mg-, protein) (mean ± s.e. mean) respectively. In forceps biopsies from vastus lateralis muscle from four healthy volunteers the values for KD and Bmax were 22.5 ± 4.4 (pM) and 16.4 ± 2.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
2
4

Year Published

1989
1989
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
3
22
2
4
Order By: Relevance
“…Kim et al [7] showed that the β1 isoform comprises only about 15–21% of the total β receptor population expressed by the soleus muscle of the adult rat and that the β2 isoform can account for essentially all β receptors in some muscles. Similar β receptor populations were found in human muscle biopsies [40, 41]. The present findings also help explain greater muscle growth efficiency in food animals supplemented with dietary β2 agonist compared to β1 agonist [4244].…”
Section: Discussionsupporting
confidence: 80%
“…Kim et al [7] showed that the β1 isoform comprises only about 15–21% of the total β receptor population expressed by the soleus muscle of the adult rat and that the β2 isoform can account for essentially all β receptors in some muscles. Similar β receptor populations were found in human muscle biopsies [40, 41]. The present findings also help explain greater muscle growth efficiency in food animals supplemented with dietary β2 agonist compared to β1 agonist [4244].…”
Section: Discussionsupporting
confidence: 80%
“…Thus, in terms of tachycardia response, if the elderly are less sensitive to the effects of isoprenaline (a non-selective 13-adrenoceptor agonist) but the effects of salbutamol (a selective P2-adrenoceptor agonist) are unchanged, this may suggest that 13-adrenoceptor responses are attenuated with preservation of 12 responses. Such a conclusion would be supported by two other recent studies (Elfellah et al, 1989;Klein et al, 1988). Klein and co-workers (1988) The heart rate response to exercise and its attenuation by ,B-adrenoceptor blockade are reduced in the elderly (Conway et al, 1971): this is probably the most reliable indicator of cardiac 1l-adrenoceptor activity.…”
Section: Discussionsupporting
confidence: 68%
“…In skeletal muscle, as much as 80-95% of the β-adrenergic receptors are of the β 2 -subtype, although most studies have detected β 1 -adrenergic receptors also (Elfellah et al 1989;Kim et al 1991;. The responsiveness to β-adrenergic stimulation depends on the density of β-adrenoceptors in the cell membrane (Böhm et al 1997;Grady et al 1997).…”
mentioning
confidence: 97%